Tendon transfer for irreparable cuff tear - Valenti, Philippe; SpringerLink (Online service) (Paris : Springer Paris, 2011)
Treatment of symptomatic irreparable cuff tear is rare, but represents a difficult challenge for the surgeon. Tendon transfer from periscapular muscles group is a therapeutic option. Many tendon transfers are reported as latissimus dorsi, teres major, split of anterior deltoid and pectoralis major. The goal of this book is to remind the biomechanical and anatomical basis of these tendon transfers and to report tips and tricks and results of these techniques. A treatment algorithm is proposed in patients who have both pain and weakness or have loss of active forward elevation or external rotation. Moreover, tendon transfer can be combined with reverse shoulder prosthesis in patients with an unstable gleno humeral arthritis.
Keywords: Medicine; Orthopedics; Surgery; Medicine & Public Health; Surgery; Orthopedics